2006
DOI: 10.3168/jds.s0022-0302(06)72130-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcemia in Dairy Cows: Meta-analysis and Dietary Cation Anion Difference Theory Revisited

Abstract: Data from 137 published trials involving 2,545 calvings were analyzed using random effects normal logistic regression models to identify risk factors for clinical hypocalcemia in dairy cows. The aim of the study was to examine which form, if any, of the dietary cation anion difference (DCAD) equation provided the best estimate of milk fever risk and to clarify roles of calcium, magnesium, and phosphorus concentrations of prepartum diets in the pathogenesis of milk fever. Two statistically equivalent and biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
181
2
18

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 237 publications
(246 citation statements)
references
References 46 publications
27
181
2
18
Order By: Relevance
“…The herds in the present study received Ca in the range from 4.9 to 10.2 g/kg DM, which, according to the model developed by Lean et al (2006), would result in considerable differences in predicted milk fever incidence. The conclusion of Lean et al (2006) is supported by the results obtained by Shappell et al (1987), where cows fed 11.6 g Ca/kg DM experienced subclinical hypocalcaemia to a much greater degree than cows fed 5.2 g Ca/kg DM. However, the results from the present study do not support the theory that a decrease in Ca intake within the range from 4.9 to 10.2 g Ca/kg DM prevents milk fever when the cows are fed Ca above the recommended level of 33 g/day.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The herds in the present study received Ca in the range from 4.9 to 10.2 g/kg DM, which, according to the model developed by Lean et al (2006), would result in considerable differences in predicted milk fever incidence. The conclusion of Lean et al (2006) is supported by the results obtained by Shappell et al (1987), where cows fed 11.6 g Ca/kg DM experienced subclinical hypocalcaemia to a much greater degree than cows fed 5.2 g Ca/kg DM. However, the results from the present study do not support the theory that a decrease in Ca intake within the range from 4.9 to 10.2 g Ca/kg DM prevents milk fever when the cows are fed Ca above the recommended level of 33 g/day.…”
Section: Discussionmentioning
confidence: 95%
“…Curtis et al (1984) found no effect of dietary Ca in commercial herds on the incidence of milk fever, although they concluded that all cows in their study were fed well above the recommendations. However, the models developed by Lean et al (2006) and Oetzel (1991) showed a large increase in predicted milk fever incidence when the Ca concentration in the diet increased up to 13 g/kg DM. The herds in the present study received Ca in the range from 4.9 to 10.2 g/kg DM, which, according to the model developed by Lean et al (2006), would result in considerable differences in predicted milk fever incidence.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations